Adsorption-desorption and degradation of insecticides clothianidin and thiamethoxam in agricultural soils. (September 2018) - Li, Yang; Su, Peidong; Li, Yadong; Wen, Kejun; Bi, Guihong; Cox, Michael
Abstract: Studied were the adsorption-desorption and degradation of two widely used neonicotinoid insecticides clothianidin and thiamethoxam in three different agricultural soils in the state of Mississippi. The adsorptions of both the neonicotinoids fit a linear isotherm model. In different soils at different depths with different moisture contents, the adsorption distribution coefficients of clothianidin and thiamethoxam were found to be 0.62 to 1.94 and 0.59–2.03 L kg −1, respectively. These distribution coefficients showed strong positive correlations with organic carbon content and pH of the soils. The desorptions of clothianidin and thiamethoxam also followed a linear isotherm, but were irreversible in respect to their adsorption isotherms. The desorption distribution coefficients ranged from 0.14 to 0.62 L kg −1, increased with the decrease of organic carbon content. The degradations of clothianidin and thiamethoxam in the soils were found to be slow with half-lives ranged from 90 to 280 and 65 to 170 d for clothianidin and thiamethoxam respectively. The degradation rates increased with the increase of the organic carbon content in the soils. The moisture content in the soils had a positive effect on the degradation rates. The Groundwater Ubiquity Scores calculated from the adsorption distribution coefficient, organic content, and half-life suggest that clothianidin and thiamethoxam have moderate to high potential to leach to groundwater. Highlights: Adsorption-desorption and degradation of neonicotinoid insecticides clothianidin and thiamethoxam in agricultural soils were studied. Both clothianidin and thiamethoxam had low adsorption distribution coefficients and high mobility in the soils. The half-lives of clothianidin and thiamethoxam in the soils ranged 90-280 and 65-170 d respectively. Calculated GUS suggests that clothianidin and thiamethoxam have moderate to high potentials to leach to groundwater.